SCRIB Promotes Proliferation and Metastasis by Targeting Hippo/YAP Signalling in Colorectal Cancer - Shen, Hengyang; Huang, Changzhi; Wu, Jingyu; Li, Jie; Hu, Tao; Wang, Zhenling; Zhang, Hongqiang; Shao, Yu; Fu, Zan (Frontiers in Cell and Developmental Biology, 2021)
The complex where scribble planar cell polarity protein (SCRIB）is located is one of the three main polar proteins, which play an important role in maintaining epithelial polarity and affecting tumor growth. However, the role of SCRIB in colorectal cancer (CRC) remains largely unknown. This study used The Cancer Genome Atlas (TCGA) data and clinical samples to determine the expression of SCRIB in CRC and explored its mechanism through bioinformatics analysis and in vivo and in vitro experiments. In this study, SCRIB was found to be highly expressed in CRC patients, and it often implies a malignant phenotype, such as proliferation, apoptosis, and epithelial-mesenchymal transition (EMT). Furthermore, we found that SCRIB may interact with the Hippo signaling pathway, and affect the phosphorylation status of YAP and the distribution in and out of the nucleus. We concluded that the increased expression of SCRIB is likely to inhibit the Hippo signaling pathway by promoting YAP phosphorylation. The role that SCRIB plays in the progression of CRC also provides an important perspective for the treatment of CRC.